2020
DOI: 10.1097/jcn.0000000000000731
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitudes, and Perceptions of Young Adults About Electronic Nicotine Delivery Systems in the United States

Abstract: Background: The causal link between cigarettes and cardiovascular disease is well known. The long-term effects of e-cigarettes are yet unknown, although early studies show biomarkers indicating inflammation and damage to endothelial cells associated with later development of cardiovascular disease. With the rapid rise in e-cigarette use, especially in young adults, it is imperative that health professionals understand the knowledge, perceptions, and motivations for use among young adults. Objectives: The purpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…This phenomenon is confirmed by studies regarding reasons for e-cigarette use that indicate that curiosity, fashionability, and social popularity are salient motives for use [ 50 52 ]; these are likely to be prevalent among lower-risk adolescents. The availability of attractive flavorings and the perception that e-cigarettes are healthier than cigarettes [ 2 , 18 , 52 ] would also tend to encourage experimentation among youths who are less influenced by a desire to take risks, be rebellious or unconventional, which characterize adolescent cigarette smokers [ 20 , 53 ]. Moreover, we observed that the prevalence of e-cigarette use fell over time relative to non-users or users of tobacco [ 54 ].…”
Section: Discussionmentioning
confidence: 60%
“…This phenomenon is confirmed by studies regarding reasons for e-cigarette use that indicate that curiosity, fashionability, and social popularity are salient motives for use [ 50 52 ]; these are likely to be prevalent among lower-risk adolescents. The availability of attractive flavorings and the perception that e-cigarettes are healthier than cigarettes [ 2 , 18 , 52 ] would also tend to encourage experimentation among youths who are less influenced by a desire to take risks, be rebellious or unconventional, which characterize adolescent cigarette smokers [ 20 , 53 ]. Moreover, we observed that the prevalence of e-cigarette use fell over time relative to non-users or users of tobacco [ 54 ].…”
Section: Discussionmentioning
confidence: 60%
“…The overriding aim of this research project was to assess prevalence and predictors of e-cigarette use and experimentation in young people aged 11-16 years in Northern Ireland (NI) Objectives: (1) An elicitation study was conducted to identify factors that influenced young peoples' motivations to use e-cigarettes; (2) a TPB-based questionnaire was constructed from the elicited beliefs; (3) the questionnaire was administered to a representative sample of young people, which determined knowledge, attitudes, prevalence of e-cigarettes use, experimentation, and identified the potential predictors of use (4), this informed the design of an framework for an educational resource to be used in post primary schools, to prevent e-cigarette uptake and experimentation [37,47]. This will be the first theory driven, evidenced based e-cigarette intervention for young people in the UK, designed to be incorporated into the curriculum [10].…”
Section: Rationale For Current Studymentioning
confidence: 99%